Pembelian impulsif pada e-commerce shopee (studi pada konsumen shopee di Jakarta Selatan) - Simon Tumanggor; Prasetyo Hadi; Rosali Sembiring (Universitas Hayam Wuruk Perbanas, 2021)
Competition in the e-commerce world is rising so competitively. Every time e-commerce offers their products or services to their consumers attractively. This condition causes the consumers to vae more alternatives to shop, especially at Shopee Indonesia. The purposeof this study was to ﬁnd out and analyze the effect of sales promotion, product quality,and electronic word of mouth on impulsive buying. This study used e-commerce Shopeeas the object. This is a quantitative study using primary data. The sample was taken using a purposive sampling technique with 75 respondents selected based on criteriathat had been determined. The data were analysed using SmartPLS. The result showedthat sales promotion have no signiﬁcant effect on impulsive buying with the value of signiﬁcance of 1,994. Another ﬁnding showed that product quality and electronic word of mouth have signiﬁcant effect on impulsive buying with the value of signiﬁcant is 2,475 and 3,679. Therefore, e-commerce Shopee must take advantage of product quality andelectronic word of mouth in order they have a competitive advantage.